Impulsive buying and personality : a behavioral genetic perspective - Bratko, Denis; Bošnjak, Michael; Butković, Ana (2008)
Buying behavior of rational homo-economicus includes the process of collecting informations about the products, judging alternatives, analyzing costs and benefits, and finally - making rational buying decisions. However, human buying behavior is often irrational, guided by wants, needs, emotions or moods. Impulsive buying is buying behavior without prior intention, and it is often guided by intense emotions and lack of planning. Prior research indicates that individual differences in the impulsive buying tendencies can be predicted from the five factor personality dimensions, e.g. from extraversion and conscientiousness. The purpose of this study was to explore the etiology of individual differences of impulsive buying behavior and to explore genetic and environmental contribution to the covariation between impulsive buying and personality. We used the classical twin design. The sample consisted of 330 twin pairs aged from 16 to 22. Twins filled in several questionnaires: 1) Impulsive buying scale (Verplanken and Herabadi, 2001) which measure impulsive buying tendencies, as well as the cognitive and emotional component of that tendencies ; 2) NEO-FFI (Costa and McCrae, 1992) which measure five broad personality domains: Neuroticism, Extraversion, Openness, Agreeableness, and Conscientiousness ; 3) Impulsivity facet scale from the NEO-PI-R (Costa and McCrae, 1992). The data analyses included the 1) univariate behavioral-genetic analysis of the impulsive buying scale which estimates the relative genetic and environmental contribution to the individual differences in impulsive buying ; and 2) several bivariate behavioral genetic analyses of impulsive buying and particular personality traits which estimate genetic and environmental overlap between impulsive buying and personality.
Projekt MZOS
ENG